2017
DOI: 10.1371/journal.pone.0184373
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sero-reactive antigens for the early diagnosis of Johne’s disease in cattle

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is the causative agent of Johne’s disease (JD), a chronic intestinal inflammatory disease of cattle and other ruminants. JD has a high herd prevalence and causes serious animal health problems and significant economic loss in domesticated ruminants throughout the world. Since serological detection of MAP infected animals during the early stages of infection remains challenging due to the low sensitivity of extant assays, we screened 180 well-characterized serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 40 publications
(56 reference statements)
3
25
0
2
Order By: Relevance
“…Since the first complete MAP genome sequence was published [ 9 ], many studies with recombinant MAP proteins have been conducted to identify potential candidates for use as diagnostic antigens that could distinguish animals with mild or early MAP infection from those uninfected [ 10 16 ]. We recently screened a set of well-characterized serum samples using a whole proteome microarray from Mycobacterium tuberculosis (MTB), and several promising candidate antigens were identified from these studies as immunogenic during MAP infection [ 17 ]. These antigens need to be further evaluated for the development of a high-throughput, diagnostic immunoassay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first complete MAP genome sequence was published [ 9 ], many studies with recombinant MAP proteins have been conducted to identify potential candidates for use as diagnostic antigens that could distinguish animals with mild or early MAP infection from those uninfected [ 10 16 ]. We recently screened a set of well-characterized serum samples using a whole proteome microarray from Mycobacterium tuberculosis (MTB), and several promising candidate antigens were identified from these studies as immunogenic during MAP infection [ 17 ]. These antigens need to be further evaluated for the development of a high-throughput, diagnostic immunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe the development of a multiplex immunoassay for simultaneous detection of antibodies specific to six candidate recombinant MAP proteins. Five of these proteins (MAP1272c, MAP1569, MAP2609, MAP2942c and MAP1201c+2942c fusion protein) were selected because they displayed the highest levels of sensitivity and specificity in our previous protein array studies [ 17 ]. Additionally, MAP2121c was selected based on previous studies that showed significant reactivity to samples from infected animals in previous ELISA studies [ 10 , 23 ] although it was not shown in the MTB array due to the absence of an ortholog in MTB [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two Map recombinant proteins identified in the EtOH extracts were tested previously for the ability to discriminate JD cows from healthy animals using protein arrays [27]. MAP_2698c was not immunogenic in those studies and MAP_0585 showed some promise as an antigen since it ranked in the upper half of all proteins examined.…”
Section: Carbohydrates But Not Proteins In the Etoh Extract Are Immumentioning
confidence: 99%
“…Paratuberculosis, also referred to as Johne’s disease, is world-wide endemic; no country or region has been found to be free of this disease (Li et al, 2016). Affected ruminants go through a long asymptomatic subclinical phase in which infection cannot reliably be detected by standard diagnostic tests (Hobmaier et al, 2019; Li et al, 2017). These subclinically infected animals can already shed MAP, thereby contaminating dairy products or meat (Sweeney, 2011).…”
Section: Introductionmentioning
confidence: 99%